2018
DOI: 10.1021/acs.energyfuels.8b01860
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Transformation in Hydrothermal Pretreatment and Steam Gasification of Sewage Sludge

Abstract: Sewage sludge is an important pool of phosphorus (P), while thermal disposal results in the enrichment of P into a final solid product. Hydrothermal treatment combined with steam gasification is an effective method to produce high-quality syngas from sewage sludge. This study discussed the transformation of P during this integrated thermochemical process based on thermodynamic calculation and the Standards, Measurements and Testing Programme analysis of solid products. The results showed that P was enriched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Moreover, IP consisted mainly of AP (97 wt% and 65 wt% for HTL-PSS-SP and HTL-SPR-SP, respectively). The phosphate form distribution was in line with those in previous studies of phosphate behavior under hydrothermal conditions [70][71][72][73]. The higher percentage of AP in the HTL solid phase from PSS could relate to the higher level of calcium in PSS (Table 1) compared to in SPR [73].…”
Section: Strategy Of Phosphate Recoverysupporting
confidence: 89%
“…Moreover, IP consisted mainly of AP (97 wt% and 65 wt% for HTL-PSS-SP and HTL-SPR-SP, respectively). The phosphate form distribution was in line with those in previous studies of phosphate behavior under hydrothermal conditions [70][71][72][73]. The higher percentage of AP in the HTL solid phase from PSS could relate to the higher level of calcium in PSS (Table 1) compared to in SPR [73].…”
Section: Strategy Of Phosphate Recoverysupporting
confidence: 89%
“…Besides, one study also suggested that gasification can be coupled with P recovery through thermochemical conversion. It was reported that P 2 O 5 could be completely converted into gas phase after 600 °C, and a total P recovery of over 80% can be achieved (Feng et al, 2018).…”
Section: ==========================mentioning
confidence: 99%
“…Favored by the low melting point of P 2 O 5 (340 °C), P in hydrochar can be vaporized under heated conditions, and thus recovered in the form of settled ash (Ahn et al, 2020). So far, only Feng et al evaluated the feasibility of P recovery through thermochemical process, steam gasification of hydrochar derived from waste activated sludge (Feng et al, 2018). It was found that phosphorus oxides can be completely converted into gas phase after 560 °C, and AP was the primary form in the gasification ash.…”
Section: Thermochemical Process 452mentioning
confidence: 99%
See 1 more Smart Citation
“…4. Chemical compositions of phosphate rock and sludge-derived ash and hydrochar: (a) typical compositions of phosphate rock from various countries [6,48]; (b) mean values and (c) violin distribution of ash compositions [6,31,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]; (d) mean values and (e) violin distribution of hydrochar compositions [14,15,22,23,28,32,45,[68][69][70][71][72][73][74][75]. EU = European Union (data from Belgium, Denmark, Germany, Poland, Spain, Sweden, and Switzerland).…”
Section: Overview Of Chemical Compositionsmentioning
confidence: 99%